2016
DOI: 10.1039/c5nr09032f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of large-area and continuous MoS2atomic layers by RF magnetron sputtering

Abstract: In this article, we report layer-controlled, continuous and large-area molydenum sulfide (MoS2) growth onto a SiO2/Si substrate by RF sputtering combined with sulfurization. A two-step process was employed to synthesize MoS2 films. In the first step, an atomically thin MoO3 film was deposited by RF magnetron sputtering at 300 °C. Subsequently, the as-sputtered MoO3 film was further subjected to post-annealing and sulfurization processes at 650 °C for 1 hour. It was observed that the number of layers of MoS2 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 53 publications
2
57
0
2
Order By: Relevance
“…18 Our group has been focusing on the synthesis of TMDCs by a sputtering-CVD method. 19,20 In this paper, we report a MoSe 2 / WSe 2 p-n heterostructure. A W lm was sputtered and then selenized to form WSe 2 , and Mo was sputtered on the WSe 2 and selenized to form a vertical MoSe 2 (n)/WSe 2 (p) junction.…”
Section: Introductionmentioning
confidence: 99%
“…18 Our group has been focusing on the synthesis of TMDCs by a sputtering-CVD method. 19,20 In this paper, we report a MoSe 2 / WSe 2 p-n heterostructure. A W lm was sputtered and then selenized to form WSe 2 , and Mo was sputtered on the WSe 2 and selenized to form a vertical MoSe 2 (n)/WSe 2 (p) junction.…”
Section: Introductionmentioning
confidence: 99%
“…EDS image showed that the atomic ratio of Mo/S was ≈13.51: 25.06 in the coating ( Figure S3, Supporting Information), which was consistent with the composition of MoS 2 . [40,41] Furthermore, X-ray diffraction (XRD) patterns further confirmed that the MoS 2 coating was prepared successfully ( Figure S4, Supporting Information), and the detected peaks located at 33.8° and 60.0° could be attributed to the (100) and (110) planes in MoS 2 , respectively. [40,41] Furthermore, X-ray diffraction (XRD) patterns further confirmed that the MoS 2 coating was prepared successfully ( Figure S4, Supporting Information), and the detected peaks located at 33.8° and 60.0° could be attributed to the (100) and (110) planes in MoS 2 , respectively.…”
Section: The Characteristic Of Morphology and Structurementioning
confidence: 70%
“…近年来TMDs的 CVD生长也取得了一定的突破 和进展, 已陆续有研究结果表明, 使用CVD法能够 制备出晶圆级别尺寸的单层连续二维TMDs薄膜、同 时其迁移率可以和微机械剥离法等"自上而下"生长 模式获得的薄膜相当 [86,87] . 总体来说, 常用的CVD法 [90] 、磁控溅射 [91] 以及 ALD [92,93] [97] 发现, 以聚甲基丙烯酸甲酯(PMMA)为 衬底的MoS 2 晶体管器件显示了更高的迁移率; Chamlagain 等 人 [98] 热蒸发(thermal evaporation) [90,100,101] 、电子束蒸发(Ebeam evaporation) [95,102] 、 磁 控 溅 射 (magnetron-sputtering) [94,96,103,] 、原子层淀积(atomic layer deposition, ALD) [92,104] 、激光分子束外延(pulsed-laser deposition, PLD) [105~107] 、 CVD [108] 以及浸涂法(dip-coating) [87,109] 等, 这些源材料薄膜制备手段都可以在目标衬底上 [92] 分别使用MoCl 5 和H 2 S作为反应 图 6 (网络版彩色)采用不同前驱体薄膜沉积工艺的TVC合成方法. (a) 通过ALD法预沉积WO 3 薄膜再硫化得到WS 2 的示意图 [93] ; (b) 通过磁控 溅射法预沉积MoO 3 薄膜再硫化得到MoS 2 的示意图 [91] ; (c) 通过热蒸发法预沉积MoO 3 薄膜再硫化得到MoS 2 的示意图 [90] ; (d) 通过电子束蒸发 法预沉积Mo薄膜再硫化得到MoS 2 的示意图 [95] ; (e) 通过浸涂法预沉积前驱体薄膜再两步硫化得到MoS 2 的示意图 [85] Figure 6 (Color online) TVC preparation method with various thin-film deposition technologies.…”
Section: 微机械剥离法unclassified